Numerical modelling of shaft lining stability - Jia, Yudan (2011)
This research project focuses on the application of numerical modelling methods to rock mechanics problems, combining theoretical, experimental and numerical modelling work. Specifically, practical finite difference modelling approach for analysing shaft lining stability through the Marl and Potash strata at Boulby mine UK has been developed using the commercially available software FLAC2D/FLAC3D (ITASCA 2008).